Thermal analysis of cylindrical concrete shell at transition boundary between regions with different reinforcement configurations. (1st February 2015) - Wang, Shen
Highlights: A study is carried out to evaluate the redistribution of thermal forces and moments at the interface of the reinforcement change. A rigorous formula is proposed to calculate thermal stresses at the interface considering thermal load redistribution. The proposed method is validated by finite element analysis in an illustrative practical example. Abstract: Within cylindrical reinforced concrete structures, such as nuclear containments, chimneys and silos, it is common to use various hoop reinforcing ratios at different elevations, in order to optimize the design. Such structures are designed for thermal effects, generally following methods provided in ACI 307 [1], the Chimney Code or ACI 349 Code Commentary [2, 3] for nuclear concrete structures. The conventional thermal analysis approach provided in aforementioned building codes is to solve the equilibrium of a given reinforced concrete section with a predetermined reinforcement configuration. However, no research has been conducted to study thermal forces and moments in transition boundary interfacing two regions with different reinforcement configurations. The compatibility at the interface between two regions with different reinforcement configurations introduces further redistribution of thermal forces and moments within the transition zone, which should be considered in the design or evaluation. In this paper, a comprehensive study has been carried out using the closed form mechanics based solution, in order to evaluate the redistribution of thermal forces and moments at the interface between two regions with different reinforcement configurations. A practical example is presented at the end of the paper to illustrate the use of the proposed method, which is then verified by using very refined finite element analysis.